2008
DOI: 10.3141/2066-12
|View full text |Cite
|
Sign up to set email alerts
|

Tolling Heavy Goods Vehicles

Abstract: Growing road network needs, rapidly increasing truck traffic, and the shortfall of traditional funding sources have contributed to two important trends in Europe: increased reliance on user fees and involvement of private capital in transport infrastructure through public–private partnerships. Since 1995 more than 20 European countries have instituted tolls on heavy goods vehicles (HGVs) using national roadways. The motivations are several: expanding sources of revenue beyond the gas tax, managing demand for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…For the case of Switzerland, Suter et al (2001) analyzed the external cost coverage of the tolling policy. In Germany Broaddus et al (2008) concluded that road traffic reduction and modal shift to rail was achieved only to a minor extent. Also for Germany, Doll et al (2007) analyzed the economic impact of the introduction of HGV tolls, concluding that there were neither undesirable price effects nor positive effects on employment due to the tolling policy.…”
Section: Previous Research On the Impact Of Road Charging On Truck De...mentioning
confidence: 99%
“…For the case of Switzerland, Suter et al (2001) analyzed the external cost coverage of the tolling policy. In Germany Broaddus et al (2008) concluded that road traffic reduction and modal shift to rail was achieved only to a minor extent. Also for Germany, Doll et al (2007) analyzed the economic impact of the introduction of HGV tolls, concluding that there were neither undesirable price effects nor positive effects on employment due to the tolling policy.…”
Section: Previous Research On the Impact Of Road Charging On Truck De...mentioning
confidence: 99%
“…As a result, their ability to affect a truck/rail modal shift is severely limited. Although tolling schemes for freight vehicles in Europe have produced increased revenue for infrastructure construction and maintenance and promoted a shift to more efficient vehicles and logistics practices, evaluations of the program have found little modal shift directly attributable to these tactics (Broaddus and Gertz 2008).…”
Section: Scale Of Modal Shift Opportunitiesmentioning
confidence: 99%
“…In 2006 were collected in Germany alone-an average tolling rate of 0.12 Euros per kilometer-and appropriated to road building and maintenance (50%), upgrades to the railway network (38%), and inland waterway maintenance (12%). Although this system did lead to more efficient freight operations and increased use of lower-emissions trucks (that are charged a lower toll rate), it is unclear whether more than a slight modal shift can be attributed to this practice (Broaddus and Gertz 2008).…”
mentioning
confidence: 99%
“…In 2006, 3 billion Euros (approximately $43.75 billion) were collected in Germany alone-an average tolling rate of 0.12 Euros per kilometer-and appropriated to road building and maintenance (50%), upgrades to the railway network (38%), and inland waterway maintenance (12%). Although this system did lead to more efficient freight operations and increased use of lower-emissions trucks (that are charged a lower toll rate), it is unclear whether more than a slight modal shift can be attributed to this practice (Broaddus and Gertz 2008). 26 FHWA Highway Statistics, 2003.…”
Section: Direct-user Feesmentioning
confidence: 99%